Investigation of the relationship between nutritional knowledge and nutritional supplement belief levels and athletic performances of elite cross-country skiers - Neslihan Akçay; Mustafa Şakir Akgül; Pınar Gobel; Hilal Doğan Güney; Mehmet Emin Yelken (Turkish Journal of Kinesiology, 2023)
The use of nutritional supplements provides support to the athlete, while the use of wrong and inappropriate supplements may adversely affect the performance of the athlete. This study investigated the relationship between the nutritional knowledge and nutritional supplement belief levels and athletic performances of elite cross-country skiers. A total of 19 elite cross-country skiers, 8 females and 11 males (mean age of 16.1±1.00 years) competing in the U-16 and U-18 categories, participated in the study. Inbody 120, 10 m, 20 m and 30 m sprint, agility, 20m shuttle run and hand grip tests were used to assess physical and psychological factors. Moreover, the Nutrition for Sports Knowledge Questionnaire (NSKQ) and the Sports Supplements Belief Scale (SSBS) were applied to the athletes. No significance was found in the comparison of the athletes in terms of Body Mass Index (BMI) classification (p>0.05). A positive relationship was found between the NSKQ and age (r=0.466; p=0.044), body fat percentage (r=0.505; p=0.027), and body fat mass (r=0.642; p=0.003) values. On the other hand, a positive relationship was found between the SSBS scale and body weight (r=0.136; p=0.009), body muscle mass (r=0.681; p=0.001), total body water (r=0.647; p=0.003), hand grip strength (right hand r=0.621; p=0.005; left hand r=0.635; p=0.003), while a negative relationship was found between the SSBS scale and 10m sprint (r=-0.589; p=0.008), 20m sprint (r=-0.606; p=0.006), 30m sprint (r=-0.480; p=0.037) and agility values (r=-0.533; p=0.019). These findings demonstrate that the sports nutrition knowledge level does not have a positive effect on athletic performance, but it has a positive effect on body muscle mass, strength, sprint, and agility values that affect athletes' athletic performances as athletes' nutritional supplements belief levels increase.